(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2017)
Between 1824 and 1925, after giving some public lectures in Italian Linguistics and Literature, Ugo Foscolo wrote some pieces known as Epoche della lingua italiana, never published on the «European Review» as he planned. In this paper is examined and offer a scholarly edition of Epoca quarta, focused on Boccaccio and Petrarca. The manuscripts used for this critical edition are now saved at Biblioteca Labronica in Livorno.